Association and prediction of red blood cell distribution width to albumin ratio in all-cause mortality of acute kidney injury in critically ill patients - Gao, Chen; Peng, Longkai (Frontiers in Medicine, 2023)
Aim: The progression of acute kidney injury (AKI) might be associated with systemic inflammation. Our study aims to explore the association and predictive value of RDW/ALB ratio (an inflammation-related indicator) in the risk of all-cause mortality and renal replacement therapy (RRT) in AKI patients admitting in the intensive care unit (ICU). Methods: A retrospective cohort study was designed, and data were extracted from the Medical Information Mart for Intensive Care III (MIMIC-III). The primary outcome was the risk of all-cause mortality (1-month, 3-month, and 12-month), and the secondary outcome was the risk of RRT. Association between RDW/ALB ratio and the risk of all-cause mortality and RRT was assessed using Cox regression analysis, with results shown as hazard ratio (HR) and 95% confidence intervals (CIs). The relationship between RDW/ALB ratio and crude probability of all-cause mortality or RRT was assessed using restricted cubic spline (RCS). Concordance index (C-index) was used to assess the discrimination of the prediction model. Results: A total of 13,856 patients were finally included in our study. In fully adjusted Cox regression model, we found high RDW/ALB ratio was associated with the increased risk of 1-month, 3-month, 12-month all-cause mortality and RRT (all P < 0.05). Moreover, RCS curves showed the linear relationship between RDW/ALB ratio and the probability of all-cause mortality and RRT, and the probability was elevated with the increase of the ratio. In addition, RDW/ALB ratio showed a good predictive performance in the risk of 1-month all-cause mortality, 3-month all-cause mortality, 12-month all-cause mortality, and RRT, with C-index of 0.728 (95%CI: 0.719-0.737), 0.728 (95%CI: 0.721-0.735), 0.719 (95%CI: 0.713-0.725), and 0.883 (95%CI: 0.876-0.890), respectively. Conclusions: RDW/ALB ratio performed well to predict the risk of all-cause mortality and RRT in critically ill patients with AKI, indicating that this combined inflammatory indicator might be effective in clinical practice.